2020
DOI: 10.1007/s10973-020-09476-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of Na2O–P2O5–Fe2O3 polyphosphate glasses

Abstract: Iron phosphate glasses are materials that can have many applications like durable matrixes in waste immobilization techniques, biomaterials, optoelectronic devices, etc. Their possible usage is related to their glass network and thermal properties. The influence of Na 2 O content on thermal properties and crystallization ability of iron phosphate glass of base composition 30 Fe 2 O 3 -70 P 2 O 5 mol% were studied. Increasing the content of Na 2 O causes a decrease in transformation temperature and increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…This large variability in composition makes phosphate glasses excellent candidates for various applications, namely in the field of metals sealing, photonics, medical and health care, vitrification of radioactive waste, etc. [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This large variability in composition makes phosphate glasses excellent candidates for various applications, namely in the field of metals sealing, photonics, medical and health care, vitrification of radioactive waste, etc. [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Both Ce 3+ and Nd 3+ and also Ca 2+ are reportedly known to act as glass formers, whereas alkali metals like Na + mostly act as network modifiers. 8,11 Contrasting effects of these loaded cations together with effective O/P determine the relative fraction of the different Q n tetrahedra in the different samples. In comparison, Nd 3+ -and Sm 3+ -loaded samples exhibit network with shorter chain lengths.…”
Section: Raman Studiesmentioning
confidence: 99%
“…7 However, it has been reported that the addition of Na 2 O-IPG generally leads to depolymerization of the glass network, which adversely affects its stability. 8 Moreover, Fe 2 O 3 addition to sodium aluminophosphate glass loaded with a mixture of metal fluorides (CsF, SrF 2 , ZrF 4 , CeF 4 , and SmF 3 ) leads to decrease in the phosphate chain length but improvement in chemical durability. 9 It has been argued that when oxygen is replaced with fluorine atom, the network connectivity in phosphate glass is decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of metal ions in coordination number 4 results in the incorporation of these ions into the glass bond, thus strengthening it, which contributes to an increase in the stability of glass with 20% dolomite addition [53]. According to literature data, the higher K H value for glass, the higher its resistance to crystallization during heating and ability to vitrify during cooling [54,55]. A lowering of the K SP , K A , and K H values implies a higher ability to crystallize, which is particularly important during the lifetime of the glasses, depending on their intended use.…”
Section: Study Of Amphibolite Glasses After the Melting Processmentioning
confidence: 99%